Identification of Air Pollution Level in Institute Technology Sumatera, South Lampung - Bambang Prasetio; Rizka Firdausi Pertiwi (Penerbit Kemala Indonesia, 2019)
Institut Teknologi Sumatera (ITERA) has the potential to generate air pollution due to the development for the next twenty years. This study aims to identify and analyse pollutant concentrations level in the ITERA. The parameters used are Sulphur dioxide (SO2), Nitrogen Dioxide (NO2), Ozone (O3), Hydrocarbon (HC), PM10, and Dust (TSP) based on PP RI No.41 at 1999 of National Ambient Air Quality Standard. The measurement results show the ambient air quality the highest concentration of pollutant occurred at the ITERA main gate is hydrocarbon which had the concentration 453 μg/m3 below the national standard at both sampling points.